2007
DOI: 10.1136/vr.161.7.226
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic imaging of loggerhead sea turtles (Caretta caretta)

Abstract: Twenty live and five dead juvenile and subadult loggerhead sea turtles were examined ultrasonographically. Ten soft tissue areas of the integument were used as acoustic windows: cervical-dorsal and cervical-ventral, left and right cervicobrachial, left and right axillary, left and right prefemoral and left and right postfemoral windows. Anatomical cross-sections were performed on the dead turtles to provide reference data. The fourth and fifth cervical vertebrae, the spinal cord, and the venous sinuses of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 3 publications
5
38
0
1
Order By: Relevance
“…In some studies, atrioventricular valves were also observed as mobile hyperechoic lines (PENNINCK et al, 1991;POSER et al, 2011). Nevertheless, another study reported the observation of only one atrioventricular valve, which appeared as a short, horizontal, echogenic line located in the center between the atrium and ventricle (VALENTE et al, 2007). The average heart rate was similar to that described in other studies (FONTENELLE et al, 2000;VALENTE et al, 2008).…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…In some studies, atrioventricular valves were also observed as mobile hyperechoic lines (PENNINCK et al, 1991;POSER et al, 2011). Nevertheless, another study reported the observation of only one atrioventricular valve, which appeared as a short, horizontal, echogenic line located in the center between the atrium and ventricle (VALENTE et al, 2007). The average heart rate was similar to that described in other studies (FONTENELLE et al, 2000;VALENTE et al, 2008).…”
Section: Discussionsupporting
confidence: 71%
“…The cardiac ventricle showed a thick, trabecular wall, as observed in California desert tortoises (Xerobates agassizi), in sea turtles (Caretta caretta) and in red-eared sliders (Trachemys scripta elegans) (PENNINCK, 1991;VALENTE et al, 2007;POSER et al, 2011). The location of the ventricle between the hepatic lobes and the thin-walled atrium was also seen in other studies (PENNINCK et al, 1991;VALENTE et al, 2008).…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations